Towards a Victimology of Consciousness - Туляков, Вячеслав Олексійович; Туляков, В. О.; Tuliakov, Viacheslav O. (Elsevier, 2025)
The rapid development of digital technologies and the intensification of hybrid warfare have transformed communication into a critical arena for both societal interaction and criminal activity. In this context, ensuring the security of communication and protecting the consciousness of individuals from manipulative influences have become pivotal challenges for modern criminology and criminal law (Tuliakov, Savinova, 2024). The emergence of the victimology of consciousness reflects a shift from traditional victimology-focused on physical, property, or social vulnerabilities-towards addressing threats to mental autonomy and free will. Drawing on the concept of "inclusive victim consciousness" as articulated by Vollhardt (2015), which emphasizes perceived similarities across victim groups to foster solidarity and positive intergroup outcomes, this article integrates these insights with the works of Ukrainian legal scholars Natalia Savinova, Yulia Kolomiyets, and Pavlo Fris on criminal law, policy and ideology, as well as the EU acquis and the European Convention on Human Rights (ECHR). It explores the criminological and legal dimensions of securing consciousness, proposes reforms de lege ferenda, and introduces the concept of legitimizing state authority through a victim-centered approach to cognitive security. Current threats include cybercrime, such as data interception, account hacking, or interference with protected systems, as well as cybersocial deviance in the form of cyberbullying, stalking, doxxing, or sextortion, and informational attacks, such as mass disinformation, deepfakes, and cognitive manipulation prevention. Disclaimer. This text was translated and edited with the assistance of AI Grok 5. All parts of this article, created with the involvement of the mentioned AI technologies, have been personally reviewed and edited.
Tuliakov V. Towards a Victimology of Consciousness [Online] / Viacheslav Tuliakov // SSRN : website. - Access mode : https://ssrn.com/abstract=5393956 or http://dx.doi.org/10.2139/ssrn.5393956 ; ttps://hdl.handle.net/11300/30376 - Publication date : 16.08.2025.
Keywords: Victimology; Disinformation; Security; Consciousness; SOCIAL SCIENCES; безпека; свідомість; дезінформація; віктимологія